ANALISIS FAKTOR BUDAYA KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PENANGANAN KARGO DI BANDARA SOEKARNO HATTA INTERNATIONAL AIRPORT - Dinar Dewi Kania; Eko Probo; Hanifah Hanifah (Institut Transportasi dan Logistik Trisakti, 2016)
Flight safety determined by various factors which related to human factors, both preflight and in-flight service. Cargo Handling is one of the contributors of airplane crash in the air. The purpose of this study are to obtain a profile of Health and Safety Culture (K3) and also to determine the factors that shape the Health and Safety Culture at the level of organizations, groups, individuals and the physical environment. This study can be categorized as a quantitative research with survey approach took place at Soekarno Hatta International Airport. Methods of analysis which employed in this research are Safety Climate Measurement Model of The British Health Safety Commission and Factor analysis . Population of this research is 110 employees of cargo warehousing with sample 53 employees using simple random sampling technique. The result of the anylisis shows that the values of Healt and Safety Culture in the cargo handling at Soekarno Hatta Airport are above the score / index average 5.0 which means that in general the whole individual in this section posses the moderate level of Healt and Safety values . The factor analysis which applied has reduced 19 factors into 11 factors that influence the Health and Safety Culture.